Fine mapping identifies NAD‐ME1 as a candidate underlying a major locus controlling temporal variation in primary and specialized metabolism in Arabidopsis. (8th March 2021) - Francisco, Marta; Kliebenstein, Daniel J.; Rodríguez, Víctor M.; Soengas, Pilar; Abilleira, Rosaura; Cartea, María E.
SUMMARY: Plant metabolism is modulated by a complex interplay between internal signals and external cues. A major goal of all quantitative metabolomic studies is to clone the underlying genes to understand the mechanistic basis of this variation. Using fine‐scale genetic mapping, in this work we report the identification and initial characterization of NAD‐DEPENDENT MALIC ENZYME 1 ( NAD ‐ ME1 ) as the candidate gene underlying the pleiotropic network Met.II.15 quantitative trait locus controlling variation in plant metabolism and circadian clock outputs in the Bay × Sha Arabidopsis population. Transcript abundance and promoter analysis in NAD‐ME1 Bay‐0 and NAD‐ME1 Sha alleles confirmed allele‐specific expression that appears to be due a polymorphism disrupting a putative circadian cis‐element binding site. Analysis of transfer DNA insertion lines and heterogeneous inbred families showed that transcript variation of the NAD‐ME1 gene led to temporal shifts of tricarboxylic acid cycle intermediates, glucosinolate (GSL) accumulation, and altered regulation of several GSL biosynthesis pathway genes. Untargeted metabolomic analyses revealed complex regulatory networks of NAD‐ME1 dependent upon the daytime. The mutant led to shifts in plant primary metabolites, cell wall components, isoprenoids, fatty acids, and plant immunity phytochemicals, among others. Our findings suggest that NAD‐ME1 may act as a key gene to coordinate plant primary and secondary metabolism in a time‐dependent manner. Significance Statement: Fine mapping identifies NAD‐ME1 as a candidate underlying a major locus controlling variation in plant metabolism and circadian clock outputs in the Bay × Sha Arabidopsis population. The mutant led to shifts in plant primary metabolites, cell wall components, isoprenoids, fatty acids, and plant immunity phytochemicals, among others. Our findings suggest that NAD‐ME1 may act as a key gene to coordinate plant primary and secondary metabolism in a time‐dependent manner.